Line Spread Test Results for Commercially Available the White Rice Porridge - Including the Effect of Four Types of Thickening Agents Added after Blending (Global Journal of Medical Research, 2023)
Lifelines are cut off during disasters As a result water gas and electricity cannot be used making it impossible to prepare meals If you always have ready-to-eat porridge you do not need to cook it and can eat it whenever you want The porridge with a lot of water causes aspiration in older people In welfare facilities and hospitals a thickener is used to adjust the viscosity of porridge so that the elderly can safely swallow it In this study we measured the thickness of commercially available porridge using the line spread test LST First the viscosity of commercially available white rice porridge was assumed Next the white rice porridge was homogenized with a mixer and the thickness was measured Two g of each of the four commercially available thickeners was added to white rice porridge homogenized with a mixer and the viscosity was measured after stirring for five minutes Viscosity measurements were taken 30 seconds 5 minutes 15 minutes and 30 minutes after each porridge placed on the measuring plate When the white rice porridge was homogenized using a mixer the viscosity became thin and there was the risk of aspiration
Keywords: commercial product; white rice porridge; lin spread test (LST); thickener